2019
DOI: 10.3390/nu11051089
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Lipemic Responses to Various Sources of Saturated and Monounsaturated Fat in Adults

Abstract: Background: Postprandial lipemia (PPL) is a cardiovascular disease risk factor. However, the effects of different fat sources on PPL remain unclear. We aimed to determine the postprandial response in triglycerides (TG) to four dietary fat sources in adults. Methods: Participants completed four randomized meal trials. For each meal trial, participants (n = 10; 5M/5F) consumed a high-fat meal (HFM) (13 kcal/kg; 61% of total kcal from fat) with the fat source derived from butter, coconut oil, olive oil, or canola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…This is in accordance with the observations of Sciarrillo et al who showed that plasma TG levels in lean and obese subjects were increased in a similar manner after a meal containing 61% of calories (51-84 g) from different fats (butter, coconut oil, olive oil, and canola oil). [34] Our results support the fact that PP TG metabolism is altered in the T2D population, because a similar lipemic response in healthy individuals would necessitate around 30-40 g of lipids. [35] Residual fasting TGRL have a mean diameter of 146 nm, which is much larger than what is reported in healthy individuals.…”
Section: Discussionsupporting
confidence: 83%
“…This is in accordance with the observations of Sciarrillo et al who showed that plasma TG levels in lean and obese subjects were increased in a similar manner after a meal containing 61% of calories (51-84 g) from different fats (butter, coconut oil, olive oil, and canola oil). [34] Our results support the fact that PP TG metabolism is altered in the T2D population, because a similar lipemic response in healthy individuals would necessitate around 30-40 g of lipids. [35] Residual fasting TGRL have a mean diameter of 146 nm, which is much larger than what is reported in healthy individuals.…”
Section: Discussionsupporting
confidence: 83%
“…After consumption of the high-fat test drinks, an increase in VLDL concentration was observed over time, while LDL and HDL concentrations were not much affected, which is in line with other trials studying other dietary lipid challenges in healthy male subjects. [33,34] We did not observe any differences in the shape of lipoprotein concentrations between the test drinks, similar to published findings where no differences in lipoprotein concentrations were seen after short-term consumption of butter, coconut oil, olive oil, and canola oil [35] , or long-term consumption of diets differing in oleic acid [36] or medium-chain FAs [37] . While we did not see a difference in small LDL size or concentration, we did observe a difference in small LDL-TAGs.…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with earlier findings in young adults, who showed similar postprandial TAG responses to four single high‐fat meals differing in SFA and MUFA content. [ 35 ] In bovine milk fat, part of the SFA are SCFA and MCFA. Those FAs can be easily absorbed and be transported directly to the liver, without incorporation into chylomicrons.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, major sources of SFA were butter and cold cuts of meat, and the major SFA was palmitic acid. Some previous studies in healthy individuals have shown that SFA (e.g., from butter, lard or coconut oil) results in a lower [ 27,35–37 ] or similar [ 38 ] increase in triglycerides than MUFA and/or PUFA. In contrast, other studies show that ingestion of MUFA (e.g., from olive oil) in test meals induces lower postprandial triglyceride concentrations than SFA (e.g., from butter or cheese) in healthy individuals, [ 39 ] in patients with impaired fasting glucose [ 40 ] and in individuals with elevated fasting triglycerides.…”
Section: Discussionmentioning
confidence: 99%